The evolving research agenda for paediatric tuberculosis infection. Issue 9 (September 2019) - Seddon, James A; Whittaker, Elizabeth; Kampmann, Beate; Lewinsohn, Deborah A; Osman, Muhammad; Hesseling, Anneke C; Rustomjee, Roxana; Amanullah, Farhana
Summary: Following exposure to tuberculosis and subsequent infection, children often progress to tuberculosis disease more rapidly than adults. And yet the natural history of tuberculosis in children, as a continuum from exposure to infection and then to disease, is poorly understood. Children are rarely diagnosed with tuberculosis infection in routine care in international settings and few receive tuberculosis infection treatment. In this Personal View, we review the most up-to-date knowledge in three areas of childhood tuberculosis infection—namely, pathophysiology, diagnosis, and treatment. We then outline what is missing in each of these three areas to generate a priority research agenda. Finally, we suggest potential study designs that might answer these questions. Understanding of pathophysiology could be improved through animal models, laboratory studies assessing the immunological responses of blood or respiratory samples to Mycobacterium spp in vitro, as well as investigating immune responses in children exposed to tuberculosis. Identification of children with sub-clinical disease and at high risk of progression to clinically overt disease, would allow treatment to be targeted at those most likely to benefit. Optimisation and discovery of novel treatments for tuberculosis infection in children should account for mechanisms of action of tuberculosis drugs, as well as child-specific factors including pharmacokinetics and appropriate formulations. To conduct these studies, a change in mindset is required, with a recognition that the diagnosis and treatment of tuberculosis infection in children is a necessary component in addressing the overall tuberculosis epidemic. Collaboration between stakeholders will be required and funding will need to increase, both for research and implementation. The consequences of inaction, however, will lead to further decades of children suffering from what should increasingly be recognised as a preventable disease.